DAMPAK KEBIJAKAN ZONASI TERHADAP KETIMPANGAN AKSES PENDIDIKAN DASAR DI INDONESIA PADA ERA DIGITAL - Ananda, Rizki; Rahmi, Aulia; Ikhlas; M. Ilham; Julia, Salsabilla (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Basic education plays a fundamental role in shaping a nation's human capital and ensuring long-term socio-economic development. In Indonesia, the implementation of the school zoning policy, formalized through Ministerial Regulation No. 14 of 2018, was intended to promote equitable access to education. However, in practice, it has intensified disparities, especially for students from low-income families and those living in areas with inadequate educational infrastructure. This study aims to analyze the impact of the zoning policy on access inequality in primary education and to examine the role of digital technology in mitigating or exacerbating these disparities. Employing a qualitative approach through library research, the study draws upon scholarly articles, policy reports, and official documents published within the last five years. Findings reveal that the zoning policy has not fully accounted for regional disparities and the digital divide, thereby reinforcing existing inequalities. The study contributes to the discourse on basic education policy by highlighting the need for a more integrative strategy—one that combines spatial equity with digital inclusion. Policy recommendations include the development of flexible zoning mechanisms tailored to local contexts and the expansion of equitable digital infrastructure and digital literacy programs to ensure just and inclusive educational access.